Synergism of ursolic acid derivative US597 with 2-deoxy-D-glucose to preferentially induce tumor cell death by dual-targeting of apoptosis and glycolysis - Wang, Jichuang (Sci Rep, 2014)
Ursolic acid (UA) is a naturally bioactive product that exhibits potential anticancer effects. The relatively safe and effective molecule intrigued us to explore a way to further improve its anti-cancer activity and tumor-targeting specificity. In the present study, a series of structural modifications of UA was achieved, which resulted in significant increase in growth inhibition on various cancer cell lines with minimal effects on normal cells. The leading molecule US597 (UA-4) caused depolarization of mitochondrial membrane potential, cell arrest in G0/G1 phase and apoptosis/necrosis in a dose-dependent manner. Structural docking suggested that the carbon chains of the modified UA derivatives compete strongly with glucose for binding to glucokinase, the key glycolysis enzyme presumably active in cancer cells. The combination of 2-deoxy-D-glucose (2-DG) and UA-4 induced cell cycle arrest in G2/M phase, promoted caspase-dependent cell death, reduced hexokinase activity, aggravated depletion of intracellular ATP, decreased lactate production and synergistically inhibited cancer cell growth in vitro (HepG2) and in vivo (H22). Collectively, our findings suggest that the structural modification enhances efficacy and selectivity of UA, and the combination of UA-4 with 2-DG produces synergistic inhibition on hepatoma cell proliferation by dual targeting of apoptosis and glycolysis.